A Curriculum Analysis of the Moral Creed: the Pattern of Moral Formation - Hidayat, Fitria; Wahidah, Nida Fatmah; Mulyadi, Yadi (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2022)
The Moral Creed curriculum in SMPN 1 of the west Bandung district contains various subject materials that point to achieving noble character in daily life, such as doing dhuha prayer, reading asmaul husna, and reading the Qur'an. Although the curriculum has been adopted based on the 2015 article 1 rule dictating to students no. 23, there are problems, such as declining student morals, students still not being used to recitation, and even cannot do it. The study aims to analyze the Moral Creed curriculum in the central west Bandung district. This study is quantitative research using the library research method. The primary data is through interviews, and secondary data is through books and other support sources. The data analysis used is analysis content. This study suggests that the Moral Creed curriculum at SMPN 1 should develop the curriculum to humanize humans and require a proper education method in the learning process.Kurikulum Akidah Akhlak di SMPN 1 Porongpong Kabupaten Bandung Barat memuat berbagai materi pelajaran yang mengarahkan pada tercaIslamic Educationnya akhlak mulia dalam kehidupan sehari-hari seperti mengerjakan sholat dhuha, membaca asmaul husna, dan membaca al-Qur’an. Meskipun sudah diterapkan kurikulum sesuai dengan peraturan Mendikbud RI No 23 Tahun 2015 Pasal 1, terdapat beberapa masalah seperti menurunnya akhlak siswa dan siswa masih belum terbiasa mengaji bahkan ada siswa yang tidak bisa mengaji. Penelitian ini bertujuan untuk menganalisis kurikulum akhlak di SMPN 1 Paronpong Kabupaten Bandung Barat Indonesia. Jenis penelitian ini termasuk penelitian kuantitatif dengan menggunakan metode library reseach, sumber data dalam penelitian ini yaitu sumber data primer melalui wawancara dan data sekunder melalui buku serta sumber pendukung lainnya. Analisis data yang digunakan yaitu konten analisis. Hasil penelitian ini menunjukan bahwa kurikulum akidah akhlak di SMPN 1 Porongpong mengembangkan kurikulum untuk memanusiakan manusia, untuk mewujudkan hal tersebut dibutuhkan metode pendidikan yang tepat dalam proses pembelajaran.